Isolation and characterization of a novel lectin with antifungal and antiproliferative activities from Sophora alopecuroides seeds - Li, Tingting; Yin, Xiaoli; Liu, Dongliang; Ma, Xiaojin; Lv, Hui; Sun, Surong (Acta biochimica et biophysica Sinica, 2012)
Sophora alopecuroides lectin (SAL), a novel lectin from the seeds of Sophora alopecuroides, was purified by ion-exchange chromatography on diethylaminoethyl (DEAE)- and carboxymethyl (CM)-Sepharose columns, followed by gel filtration on a Sephadex 75 10/300 GL column. SAL was found to be a monomer of 39916.3 Da, as determined by tricine-sodium dodecyl sulphate-polyacrylamide gel electrophoresis and high-performance liquid chromatography (HPLC). The N-terminal 10-amino acid sequence of SAL, KPWALSFSFG, resembles those of other legume lectins. SAL exhibits hemagglutinating activity against rabbit erythrocytes at 11.9 μg/ml. Its hemagglutinating activity is stable in the pH range 7-11 and in the temperature range 30-90°C, and is stimulated by Mn(2+). The hemagglutinating activity of SAL is most potently inhibited by 50-mM d-galactose. SAL suppresses mycelial growth in Penicillium digitatum and Alternaria alternata; the IC(50) of the antifungal activity toward P. digitatum and A. alternata were found to be 3.125 and 3.338 μM, respectively. SAL suppresses the proliferation of human cervical cancer cells (HeLa) at an IC(50) of 6.25 μM (P< 0.05). But it has no inhibiting effect on bacteria. This is the first report of a lectin from seeds of S. alopecuroides.